2023
DOI: 10.1021/acs.jpcc.3c02039
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Effect of Cation Distribution at Tetrahedral Sites in ZnCo2O4 Spinel Nanostructures on the Charge Transfer Ability and Electrocatalytic Activity toward Ultrasensitive Detection of Carbaryl Pesticide in Fruit and Vegetable Samples

Abstract: The recent advancement in designing novel spinel nanostructures has opened virtually infinite possibilities for the development of high-performance electrochemical sensors to detect target species. The electrocatalytic activity of spinel structures can be enhanced by tuning the cation distribution; however, the role of cation distribution at tetrahedral ions on the electrochemical sensing responses has rarely been considered. Herein, the effect of cation distribution at tetrahedral sites (T d ) in the spinel n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 58 publications
(105 reference statements)
2
4
0
Order By: Relevance
“…The absorption capacity of each modified electrode can be calculated from the values of the observed slope of I pa versus v for SPCE-A400, SPCE-A600, and SPCE-A800 being 3.18 × 10 –5 , 2.2 × 10 –5 , and 1.22 × 10 –5 mol cm –2 , respectively. In comparison, previous works have determined the value of adsorption capacity of electrochemical sensors based on modified electrodes for carbaryl detection and obtained comparable results with our work. , Based on these results, it can be concluded that the modified electrodes based on SPCE-modified AuNR400 displayed the largest capacity for carbaryl adsorption on the electrode surface among other developed electrodes.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…The absorption capacity of each modified electrode can be calculated from the values of the observed slope of I pa versus v for SPCE-A400, SPCE-A600, and SPCE-A800 being 3.18 × 10 –5 , 2.2 × 10 –5 , and 1.22 × 10 –5 mol cm –2 , respectively. In comparison, previous works have determined the value of adsorption capacity of electrochemical sensors based on modified electrodes for carbaryl detection and obtained comparable results with our work. , Based on these results, it can be concluded that the modified electrodes based on SPCE-modified AuNR400 displayed the largest capacity for carbaryl adsorption on the electrode surface among other developed electrodes.…”
Section: Resultssupporting
confidence: 86%
“…The mechanism of carbaryl oxidation on the surface of SPCE-modified AuNRs can be deduced following the two processes: (1) the hydrolysis of carbaryl molecules into 1-naphthol in an alkaline condition and (2) the oxidation of hydroxyl (OH – ) functional groups within the 1-naphthol chemical structure by removing 1 electron and 1 proton (H + ) with the corresponding anodic oxidation peak at 0.2 V. The mechanism of carbaryl oxidation at the surface of SPCE-modified AuNR is illustrated in Figure d. Furthermore, recent studies demonstrated the oxidation of 1-naphthol using SPCE-modified metal nanoparticles, and the metal oxide composite occurs at 0.4 V as reported in ref and at 0.5 V as reported in ref . Based on this result, it can be inferred that the SPCE-modified facet-controlled anisotropic gold nanoparticles provide faster electron transfer kinetics to oxidize carbaryl molecules than bare SPCE.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…More interestingly, most of the nano/microflakes are connected through both edge-to-flat-surface and edge-to-edge conjunctions, which can be applied as an outstanding electro-bridge to promote electron transfer between the electrode and analyte, and thus enhancing the electrochemical sensing performance. 25 Electrochemical properties of unmodified and NFO-modified SPE electrodes.-To define the role of NFO NFs in enhancing peak current response as well as electrochemical active surface area and reducing peak-to-peak potential, the electrochemical performance of unmodified and modified SPE electrodes was scrutinized by CV technique in a benchmark redox probe Fe(CN) 6 ] 3-/4at a scan rate of 50 mV s -1 . Figure 2a illustrates the CV curves of the bare SPE and NFO/SPE in 0.1 M KCl containing 5 mM [Fe(CN) 6 ] 3-/4-.…”
Section: Resultsmentioning
confidence: 99%
“…27–29 In recent work, our group developed a series of electrochemical sensors based on AFe 2 O 4 (A = Zn, Co, Mn, Ni, Cu), BCo 2 O 4 (B = Zn, Cu), and ZnFe 2 O 4 /ZnO hetero-nanostructures for the highly sensitive detection of various types of analytes including chloramphenicol, furazolidone, carbaryl, and clenbuterol. 30–34 Therefore, the electrochemical sensing platform and spinel oxide nanostructures are expected to provide a promising combination for quickly and accurately analysing as well as quantifying pharmaceutical tablets.…”
Section: Introductionmentioning
confidence: 99%